Capacity building in Nepal - Dawe, Russell Eric; Stobbe, Karl; Pokharel, Yagya Raj; Shrestha, Shrijana (Canadian Medical Education Journal, 2016)
Healthcare providers from high-income countries often want to help underserved populations, but providing clinical care is not always a sustainable approach. Patan Academy of Health Sciences (PAHS), in Nepal, has taken an innovative approach to capacity building in healthcare. PAHS has partnered with rural family doctors from Canada to provide clinical bedside teaching to medical students in PAHS’s rural program, thereby making a sustainable contribution to healthcare in Nepal.